2014
DOI: 10.1016/j.febslet.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X increases immune cell recruitment by induction of chemokine SDF‐1

Abstract: a b s t r a c tHepatitis B virus X protein is a major factor in the HBV-induced disease developments. Stromal cellderived factor-1 is a small cytokine that is strongly chemotactic for lymphocytes. We explored the role of HBx on recruitment of HBV-induced virus-nonspecific immune cells into liver. Immune cell recruitment and SDF-1 expression level significantly increased in livers of HBx-transgenic mice and X-box binding protein-1 significantly increased SDF-1 gene expression. Finally, we confirmed that immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…One such chemokine involved is stromal cell-derived factor-1 (SDF-1), which is induced by HBx via endoplasmic reticulum stress. The recruited immune cells in the liver will engender a more severe chronic hepatitis [ 22 ].…”
Section: Pathwaysmentioning
confidence: 99%
“…One such chemokine involved is stromal cell-derived factor-1 (SDF-1), which is induced by HBx via endoplasmic reticulum stress. The recruited immune cells in the liver will engender a more severe chronic hepatitis [ 22 ].…”
Section: Pathwaysmentioning
confidence: 99%
“…Biliary epithelial cells secrete CXCL12, and the increased expression of this ligand in interlobular and septal bile ducts and proliferated bile ductules can recruit inflammatory and immune cells to the inflamed liver . The CXCL12/CXCR4 axis has been implicated in the migration of immune cells to the liver in patients with chronic hepatitis B and C, PBC, PSC and autoimmune hepatitis . CXCL14 has been proposed as a natural inhibitor of CXCL12, and CXCR7 may also naturally modulate this pro‐inflammatory axis .…”
Section: Chemokine Ligands and Receptors In Autoimmune Hepatitismentioning
confidence: 99%
“…Interestingly, recent studies have shown that hepatitis B virus X protein (HBx) is a main factor in the development of HBV-induced disease. HBx increases endoplasmic reticulum (ER) stress-dependent CXCL12 expression and mediates HBV-induced recruitment of immune cells into the liver via CXCL12 signaling ( Cho et al, 2014 ). Furthermore, HBx is involved in the occurrence and development of HBV-related HCC through the CXCL12/CXCR4/β-catenin signaling axis ( Wang C. et al, 2017 ).…”
Section: The Regulatory Role Of Cxcr4 and Its Ligand In Hepatitismentioning
confidence: 99%